Impact of Academic Competence on Air Traffic Safety Improvement at AirNav Indonesia JATSC Branch - Ridha Aulia; Martha Saulina; Susi Suhardianti (CV. AFDIFAL MAJU BERKAH, 2026)
Aviation safety is a critical aspect of air traffic services, particularly in operational units with high traffic density and complexity such as the Jakarta Air Traffic Service Center (JATSC). The continuous growth of air traffic volume requires Air Traffic Controllers (ATC) to possess strong academic competence to support accurate, consistent, and risk-aware decision-making. This study aims to examine the level of academic competence among ATCs and analyze its influence on the improvement of air traffic safety at Perum LPPNPI JATSC Branch. A quantitative research method with an associative approach was employed. The research sample consisted of 98 ATCs selected using a random sampling technique. Data were collected through structured questionnaires and analyzed using validity and reliability tests, descriptive statistics, simple linear regression, and coefficient of determination with the assistance of SPSS software.